New Directions for Law in Australia 2017
DOI: 10.22459/ndla.09.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Is Criminal Law Reform a Lost Cause?

Abstract: I would like to thank Michael Potts and Zoe Brereton for research assistance. 2 Under its parent Act, The Law Commission (England and Wales) was tasked with keeping the law under review 'with a view to its systematic development and reform, including in particular the codification of law':

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Bystander sousveillance can make meaning of aggregate police data reported in the mainstream media through a qualitative critique, providing pretext of what happens before a crime occurs (Quinney, 1995) and context of the criminalisation process (Bronitt and McSherry, 2010; Presdee, 2000). At the same time, the Jackson Reed video showed that mainstream media reports of the policing of major public events reflect police and event organisers’ view of safety at a ‘whole of crowd’ level, while spectators are more concerned about personal safety (Tomsen and Markwell, 2009: iii).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bystander sousveillance can make meaning of aggregate police data reported in the mainstream media through a qualitative critique, providing pretext of what happens before a crime occurs (Quinney, 1995) and context of the criminalisation process (Bronitt and McSherry, 2010; Presdee, 2000). At the same time, the Jackson Reed video showed that mainstream media reports of the policing of major public events reflect police and event organisers’ view of safety at a ‘whole of crowd’ level, while spectators are more concerned about personal safety (Tomsen and Markwell, 2009: iii).…”
Section: Methodsmentioning
confidence: 99%
“…Police file their own briefs of evidence, and police oversight bodies often only have jurisdiction over ‘serious misconduct’ (NSW Council for Civil Liberties, 2017). Public order matters 1 provide important perspectives on the procedures of criminalisation, the characteristics and apparatus of criminal liability and the cultural, social and political context of law enforcement (Bronitt and McSherry, 2010). At the same time, the basis of the criminal law is the responsibility and culpability of the individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis is crucial for understanding the international aspects of criminal justice and clarifying the issues of jurisdiction and the application of international criminal law. S. Bronitt and B. McSherry (2017) provide an updated perspective on the basic principles of criminal law in their edition "Principles of Criminal Law 4e", considering them in terms of modern challenges and changes in the legal sphere. Their contribution is significant in the context of adapting traditional principles to modern realities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Examples observed included tree-style maps to represent key aspects of individual litigated legal cases, 48 the elements necessary to making a case, 49 elements of financial contracts, 50 and to prompt lawyers on enquiries that should be undertaken on behalf of the client to ensure due diligence in property matters. 51…”
Section: Concept Map 12mentioning
confidence: 99%